Naturologia e espiritualidade: indícios dos valores do movimento da Nova Era entre naturólogos formados no Brasil - Stern, Fábio Leandro (2015)
This thesis aimed to investigate the relationship between Naturology in Brazil and the New Age movement, starting from the hypothesis raised by Teixeira that the emergence of Naturology in Brazil is related to the New Age arrival to this country. To this end, 292 questionnaires were applied in naturologists graduated by the two Brazilian universities with Naturology courses recognized by the Brazilian Ministry of Education. In order to measure the degree of adherence to the New Age movement, a Likert scale was applied with 25 items related to major trends of the New Age movement highlighted by Hanegraaff. The results showed 51.7% of the naturologists objectively consider themselves newagers, and the active naturologists are precisely those who demonstrate the greatest degree of identification with the title. It was also verified that the Likert scale results were high in all categories, with averages exceeding 3 (out of 4)